The co-construction of the social situation of development and its impact on EFL teachers? thinking and practical activity - Agnoletto, Matheus André (2024)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão, Programa de Pós-Graduação em Inglês: Estudos Linguísticos e Literários, Florianópolis, 2024.